Personality Pathways to Mortality: Interleukin-6 Links Conscientiousness to Mortality Risk - O’Súilleabháin, Páraic S. (Brain Behav Immun, 2021)
Personality is associated consistently with mortality hazards, but the physiological pathways are not yet clear. Immune system dysregulation may be one such pathway due to its role in age-related morbidity and mortality. In this preregistered study, we tested whether interleukin-6 (IL-6) and C-reactive protein (CRP) mediated the associations between personality traits and mortality hazards. The sample included 957 participants (M ± SD = 58.65 ± 11.51 years; range = 35 – 86 years) from the Midlife in the United States Survey that had 14 years of follow-up. Higher conscientiousness was associated with lower mortality hazards, with each one standard deviation higher conscientiousness associated with a 35% lower mortality risk. IL-6, but not CRP, partially mediated this association, with IL-6 accounting for 18% of this association in the fully adjusted model. While there was initial evidence that the biomarkers mediated both neuroticism and agreeableness and mortality risk, the indirect effects were not significant when controlling for the sociodemographic variables. Taken together, higher conscientiousness may lead to a longer life partially as a result of lower IL-6. This work highlights the importance of biological pathways that link personality to future mortality risk.